العنف الأسري وعلاقته ببعض المتغيرات الديموغرافية للأسرة لدى طلبة التعليم الأساسي في محافظة اللاذقية - بركات, غسان (Latakia University Journal - Arts and Humanities Sciences Series, 2018)
هدفت الدارسة التعرف إلى العنف الأسري (نسبة شيوعه، أسبابه) من جهة، وعلاقته ببعض المتغيرات الديمغرافية للأسرة لدى طلبة التعليم الأساسي في محافظة اللاذقية (ريف ومدينة) من جهة أخرى. واستخدمت الدارسة المنهج الوصفي التحليلي، في دراسة العينة التي اشتملت على (196) طالباً وطالبة من طلبة التعليم الأساسي (الحلقة الثانية) في محافظة اللاذقية للعام الدراسي 2010/2011. ولتحقيق هدف الدارسة صممت استبانة احتوت (25)عبارة، لدراسة العلاقة بين العنف الأسري وبعض المتغيرات الديمغرافية في الأسرة. أظهرت النتائج أن العنف اللفظي أكثر أنواع العنف شيوعاً بين الطلبة بنسبة (73%)، وتبين أن النسبة الأعلى التي ركز عليها الأطفال في أسباب العنف الأسري الذي يتعرضون له بشكل دائم تعلقت بالتلفظ بكلمات نابية بنسبة (61.69%)، وأظهرت النتائج أيضاً عدم وجود فروق دالة بين الطلبة تبعاً لمتغير الجنس، ووجود فروق دالة بين الطلبة تبعاً لمغير مكان الإقامة عند مجال العنف النفسي لصالح طلبة المدينة. كما قدمت الدارسة مقترحات للحد من ظاهرة العنف الأسري. The Goal of the study is to identify domestic violence (percentage of prevalence, causes) on the one hand, and its relationship to some demographic variables of the family among the students of basic education in the province of Lattakia on the other. The study uses descriptive and analytical approach, in a study sample that included the (196) students, students of basic education in the province of Lattakia for the academic year 2010/2011. To achieve the goal of the study was designed to identify contained (25) a paragraph, to study the relationship between domestic violence and some demographic variables in the family. The results showed that verbal violence is more common among students by (73%), and found that the highest percentage highlighted by the children in the causes of domestic violence they are exposed to constantly concerned verbal abuses by (61.69%), and the results showed that there are no significant differences among the students according to gender, the presence of significant differences between students depending on the place of residence changed when the field of psychological violence for the benefit of students of the city. The Study also presented recommendations to reduce the phenomenon of domestic violence.